ADHD Assessment in College Students: Psychologists' Adherence to DSM-5 Criteria and Multi-Method/Multi-Informant Assessment. (April 2019) - Weis, Robert; Till, Christina H.; Erickson, Celeste P.
The evidence-based assessment of attention-deficit/hyperactivity disorder (ADHD) depends on adherence to Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) diagnostic criteria and reliance on multi-method/multi-informant data. Although nearly all psychologists endorse these practices, college students with ADHD may lack documentation supporting their diagnoses. We reviewed the documentation submitted by 214 undergraduates diagnosed with ADHD and receiving academic accommodations for this condition. Their clinicians also completed a checklist that described their assessment procedures. Relatively few psychologists assessed all DSM-5 criteria, based on either the psychologist's self-reported assessment procedures (23.4%), written documentation (14.0%), or multi-method/multi-informant data (10.3%) such as educational/medical records, results of rating scales, or interviews with other informants. Psychologists were least likely to assess students' areas of impairment or to rule out alternative causes for students' self-reported symptoms. This lack of adherence to DSM-5 criteria and overreliance on students' self-reports can threaten the reliability of diagnosis and the appropriateness of medication and accommodations that follow.